MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI SDN 001 KEMPAS JAYA - Herliati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines the effectiveness of the problem-based learning model to improve students' critical thinking skills. This model can train students to solve problems through the knowledge they already have. Problem-based Learning or PBL is an approach to the teaching and learning process by using a real problem that occurred in life as a context for students to explore their knowledge regarding critical thinking way. The research was Classroom Action Research (CAR) with a research design model of Kemmis and Mc. Taggart. The research was conducted at SDN 001 Kempas Jaya. The subjects involved 25 sixth-grade students. In Cycle I, before applying problem-based learning, it showed critical thinking skills with classical completeness of 56% with an average score of 67.2. While, in Cycle II, the classical completeness value was 88% with an average score of 77.3. In general, the problem-based learning model could improve students' critical thinking skills, which influenced on the improvement of students’ learning outcomes in the teaching and learning process.